Primary Pyomyositis: Contact Sports as the Rare Risk Factors - Behzad Amoozgar; Varun Kaushal; Bhaveshkumar Garsondiya (Case Reports in Infectious Diseases)
Primary pyomyositis is an infectious disorder that mostly involves children and adults. Direct injury to the muscle or any traumatic process that can cause bacteremia has been described as the common risk factor. Contact sports without direct contusion or injury to the muscle is an uncommon culprit for the manifestation of this disease. In our case, a young male athlete presented to the emergency room with vague signs and symptoms including right leg muscle pain and fever. He denied any direct injury or contusion of the muscle. CT scan was done and showed edematous gluteus minimus muscle. MRI as one of the best tools for investigating soft tissues was done and exhibited myositis. Blood culture became positive for the methicillin-susceptible Staphylococcus aureus. Appropriate antibiotics were started, and the patient condition was improved. Considering prominent risk factors, early diagnosis and treatment of pyomyositis are major key factors for the management of these infectious conditions as it may cause loss of the limb or even result in mortality.